Coalbed methane systems and hydrochemical signature of produced water in the Zhijin Block, Western Guizhou province, China: Implications for gas production - Chen Guo; Xiankuo Yang; Yong Qin; Pengrui Lyu; Reza Taherdangko; Lingling Lu; Xi Cheng (Unconventional Resources, 2025)
The development of coalbed methane (CBM) resources is controlled by the characteristics of CBM systems. Three types of superposed CBM systems, including growing, decaying, and stable, were recognized in the Zhijin Block of western Guizhou, South China, each exhibiting differences in hydrodynamic conditions. Insufficient understanding of these differences currently hinders the efficient CBM development in the Zhijin Block. Hydrochemical signatures of the Zhucang and Agong synclines were investigated using produced water samples from CBM wells, which develop a decaying-type and a stable-type CBM system, respectively. The hydrochemical characteristics and formation processes of the produced water, along with their implications for the CBM development, were analyzed. Produced water chemistry exhibits marked contrasts between the Agong and Zhucang synclines, with the former exhibiting high SO42− concentration and the latter exhibiting high Cl−, HCO3−, Na+, and TDS concentrations. Based on the theoretical calculations, the groundwater flow velocity in the coal seams of the Agong syncline is 7.49 times that of the Zhucang syncline. As a result, the CBM enrichment and production potential in the Agong syncline is lower. Three genetic mechanisms of hydrochemical evolution affecting the water qualities were identified: the retention (salt accumulation) process, the desulfurization (reduction) process, and the recharge (oxidation) process. The coal measure water in the Agong and Zhucang synclines undergo oxidation and reduction process after receiving surface water replenishment, respectively. Key hydrochemical parameters, including γNa+/γCl−, γCl−/γHCO3-, γCl−, and γSr2+, exhibit a power function relationship with peak daily gas production. Critical values of the key hydrochemical parameters, which indicate gas production potential, can be extracted based on this relationship. For example, when the γNa+/γCl− is greater than 142, gas production rates are generally low, predominantly observed in CBM wells within the Agong syncline. These findings enable a better understanding of variations in CBM accumulation and production potential across the Zhijin Block, and provide a basis for optimizing CBM development plans and technologies under conditions of superposed CBM systems.